2020
DOI: 10.1007/s12565-020-00543-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the anterolateral ligament: a complex of fibrous tissues spread to the anterolateral aspect of the knee joint

Abstract: The anterolateral ligament (ALL) has recently received considerable attention as a key structure maintaining the rotational stability of the tibia. However, the morphology of the ALL, particularly the proximal attachment, is controversial. This study aimed to elucidate the morphological relationship between the ALL and its adjacent structures. A total of 25 knees from 22 cadavers were used in the current study. One knee was set at 30°, 60° and 90° of flexion. Stretched or winkled fibrous tissues were then obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…One of the debatable issues regarding ALL is whether it is a distinct ligamentous structure or a simple capsular thickening. This controversy resulted from the inconsistent findings related to the presence of ALL in previous cadaveric studies, which ranged from 0% to 100%[ 8 , 15 , 16 ]. In a study reported by Claes et al [ 3 ], ALL was identified in almost all the cadaveric knees (40 of 41, 97.6%).…”
Section: Prevalence Of Allmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the debatable issues regarding ALL is whether it is a distinct ligamentous structure or a simple capsular thickening. This controversy resulted from the inconsistent findings related to the presence of ALL in previous cadaveric studies, which ranged from 0% to 100%[ 8 , 15 , 16 ]. In a study reported by Claes et al [ 3 ], ALL was identified in almost all the cadaveric knees (40 of 41, 97.6%).…”
Section: Prevalence Of Allmentioning
confidence: 99%
“…Several cadaveric studies reported that ALL was identified as a distinct ligamentous structure, separate from the anterolateral capsule. However, some studies reported only a thickening of the articular capsule or a complex of fibrous tissue on the anterolateral capsule[ 3 , 8 ]. With these inconsistent findings, questions regarding the anatomical implications of ALL reconstruction for the restoration of rotatory stability, and the surgical technique for proper tunnel placement may emerge.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the humeroulnar joint capsule could not be separated from the tendinous septum between the flexor pronator muscles and these deep aponeuroses, and some of these complexes were the anterior bundle of the ulnar collateral ligament (Hoshika et al 2019 ). In other articular systems apart from the elbow, such as knee and ankle, recent anatomical studies have also shown that the so-called “ligament” can be precisely defined based on pericapsular structures, such as the joint capsule, tendon, and aponeurosis (Amaha et al 2019 ; Nasu et al 2020 ).…”
Section: Dynamic Stabilization Mechanism Via the Iliofemoral Ligamentmentioning
confidence: 99%
“…Більшість дослідників сходиться у тому, що легше візуалізувати антеролатеральну зв'язку при зігнутому колінному суглобі. Так, одні дослідники проводять ультрасонографічне дослідження АЛЗ у положенні згинання колінного суглоба під кутом 90° [20], інші -під кутом 30° [17] [25]. З іншого боку, наявність у місці прикріплення до великогомілкової кістки за даними частини з вчених цієї ж групи в попередніх роботах "ентезису" та некальцифікованого фіброзного хряща свідчить про суттєві механічні навантаження [24] та є типовою для зони прикріплення до кістки зв'язок та сухожилків [26,27].…”
Section: результати та їх обговоренняunclassified